1991
DOI: 10.1093/ajh/4.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Sudden Cardiovascular Death in Hypertensive Patients: Mortality Results From the MAPHY Study

Abstract: In a randomized primary prevention trial including 3,234 men with mild to moderate uncomplicated hypertension, the effect of the beta-blocker metoprolol or a thiazide diuretic as an initial antihypertensive therapy was compared regarding the risk of sudden cardiovascular death during a follow-up ranging from 2.3 to 10.8 years (median of 4.2 years). Only men aged 40 to 64 years were included in the study. The randomization of patients into the metoprolol (n = 1,609) or diuretic group (n = 1,625) was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 0 publications
1
22
0
4
Order By: Relevance
“…Sport also posed a high risk, as already reported [32,33] . Several studies have shown that imbalances of sympathetic and parasympathetic tone can provoke coronary spasm or ventricular fibrillation [34][35][36] , and regular exercise and a certain kind of beta-blocking agent can suppress the incidence of sudden death even for those without myocardial infarction [33,37] . These findings suggest that autonomic stabilization may prevent sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…Sport also posed a high risk, as already reported [32,33] . Several studies have shown that imbalances of sympathetic and parasympathetic tone can provoke coronary spasm or ventricular fibrillation [34][35][36] , and regular exercise and a certain kind of beta-blocking agent can suppress the incidence of sudden death even for those without myocardial infarction [33,37] . These findings suggest that autonomic stabilization may prevent sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on coronary events, however, is much less clear. Metoprolol reduced coronary events, 14 and sudden deaths 15 much more effectively than diuretics in the MAPHY Study and propranolol had some impact in the MRC study 16 when silent MIs were included. 17 However, atenolol was not very effective in the Cooper and Warrender Study, 18 the HAPPHY study 19,20 or the MRC elderly study.…”
Section: Primary and Secondary Preventionmentioning
confidence: 93%
“…Однако доказательная база в отношении влияния БАБ на вероятность осложнений АГ строится на основании крупных РКИ, в которых ис-пользовали в основном пропранолол, метопролола тарт-рат, атенолол -MAPHY (метопролола тартрат), MRC (атенолол), HAPPHY (метопролола тартрат, атенолол, пропранолол), STOP-Hypertension сравнение с плаце-бо (метопролола тартрат, пиндолол, атенолол) [6][7][8][9]. Прямых сравнений в длительных РКИ между разными БАБ у больных с АГ не проводилось.…”
Section: артериальная гипертонияunclassified